Chemogenomic approach to identifying nematode chemoreceptor drug targets in the entomopathogenic nematode Heterorhabditis bacteriophora. (June 2021) - Motaher, Reeham; Grill, Emilia; McKean, Elise; Kenney, Eric; Eleftherianos, Ioannis; Hawdon, John M.; O'Halloran, Damien M.
Graphical abstract: Highlights: Describe a chemogenomic pipeline for the identification of anthelmintics that target nematode chemoreceptor GPCRs. Identify differentially expressed GPCRs in Heterorhabditis bacteriophora after host-activation. Characterize candidate anthelmintics and substrates in Heterorhabditis bacteriophora . Abstract: Parasitic nematodes constitute one of the major threats to human health, causing diseases of major socioeconomic importance worldwide. Recent estimates indicate that more than 1 billion people are infected with parasitic nematodes around the world. Current measures to combat parasitic nematode infections include anthelmintic drugs. However, heavy exposure to anthelmintics has selected populations of livestock parasitic nematodes that are no longer susceptible to the drugs, rendering several anthelmintics useless for parasitic nematode control in many areas of the world. The rapidity with which anthelmintic resistance developed in response to these drugs suggests that increasing the selective pressure on human parasitic nematodes will also rapidly generate resistant worm populations. Therefore, development of new anthelmintics is of major importance before resistance becomes widespread in human parasitic nematode populations. G-Protein Coupled Receptors (GPCRs) represent an important target for many pharmacological interventions due to their ubiquitous expression in various cell types. GPCRs contribute to numerous physiological processes, and their ligand binding sites located on cell surfaces make them accessible targets and attractive substrates in terms of druggability. In fact, ∼35 % of Food and Drug Administration (FDA) and European Medicines Agency (EMA) approved drugs target GPCRs and their associated proteins, with over 300 additional drugs targeting GPCRs at the clinical trial stage. Nematode Chemosensory GPCRs (NemChRs) are unique to nematodes, and therefore represent ideal substrates for target-based drug discovery. Here we set out to identify NemChRs that are transcriptionally active inside the host, and to use these NemChRs in a reverse pharmacological screen to impede parasitic development. Our data identified several NemChRs, and we focused on one that was expressed in neuronal cells and exhibited the highest fold change in transcription after host activation. Next, we performed homology modelling and molecular dynamics simulations of this NemChR in order to conduct a virtual screening campaign to identify candidate drug targets which were ranked and selected for experimental testing in bioassays. Taken together, our results identify and characterize a candidate NemChR drug target, and provide a chemogenomic pipeline for identifying nematicide substrates.